2009
DOI: 10.3921/joptom.2009.215
|View full text |Cite
|
Sign up to set email alerts
|

Myopia Control with Orthokeratology Contact Lenses in Spain (MCOS): Study Design and General Baseline Characteristics

Abstract: PURPOSE:Although previous studies suggest that orthokeratology contact lens wear slows eye growth in children with progressing myopia, some limitations in the methodology employed have become evident. Furthermore, the safety of this modality of visual correction has not been assessed. The study "Myopia Control with Orthokeratology Contact Lenses in Spain" (MCOS) is being conducted to compare axial length growth between white European myopic children wearing orthokeratology contact lenses (OK) and wearing dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Prospective and randomized investigations are warranted to overcome the limitations of this retrospective study. 11 In addition, although no serious complications such as microbial keratitis or corneal abrasion were reported, the safety of overnight orthokeratology should be further addressed. A formal prospective report on the incidence of adverse events association with overnight orthokeratology contact lenses specifically used to treat myopia is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective and randomized investigations are warranted to overcome the limitations of this retrospective study. 11 In addition, although no serious complications such as microbial keratitis or corneal abrasion were reported, the safety of overnight orthokeratology should be further addressed. A formal prospective report on the incidence of adverse events association with overnight orthokeratology contact lenses specifically used to treat myopia is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal refractive therapy has proved to be efficacious to slow myopia progression in children in at least 5 different peer reviewed and published studies around the world [10][11][12][13][14][15], including one controlled randomized clinical trial [16][17][18]. However, these studies have been conducted only in early onset myopia.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 This is associated with changes in the corneal surface by orthokeratology and could be related to lower ocular growth already confirmed in a report of cases 10 and in controlled trials in Hong Kong, Japan, U.S. and Spain. [11][12][13][14] Furthermore, recent clinical studies have also showed that the peripheral refractive profile along the horizontal meridian could also play a role in the onset and progression of myopia in children, with the premyopic eyes showing hyperopic or less myopic peripheral refractive patterns. 15 Over the last decade, refractive surgery has emerged as an attractive option to people with low-to-moderate refractive errors, particularly in myopic patients.…”
mentioning
confidence: 97%